Biology Students Perception of Learning Ethnobotany based on Electronic Learning (E-Learning) - Nasution, Aswarina; Hasairin, Ashar; Arwita, Widya (Journal of physics. Conference series, 2020)
Internet connection has become useful part of education. Many teachers and lecturers create electronic learning to support their learning-teaching process. The aim of this research is to know the student's perception of e-learning in ethnobotany. Descriptive research was used to get the data by giving 28 students questioners. Based on the questioners that have been analyzed, researcher found that 100% of students know about e-learning and have access to e-learning 96.43% of students state that e-learning can helps the learning process and 100% of students agree that e-learning help them to access the subject matter. There are 5 obstacles identified from the survey including connection problem (96.42%), the lack of information about how to use e-learning (50%), interaction problem with lecturers through e-learning (21.43%), lack of discipline to use e-learning to study (14.29%), and don't know how to use e-learning (7.14%). Further research is needed to overcome this problems.